Taxation and "Abnormal" International Capital Flows - Levi, Maurice D. (Journal of Political Economy, 1977)
If the choice of domestic versus foreign money and capital market instruments was on the basis of covered yields, funds would universally flow in one direction, from the smallest incentive, to the instruments of highest yields. This paper shows the consequences of different rates of taxation on interest and on exchange gains, the two components of foreign yields. By reference to the U.S.-Canadian situation it is shown how we might observe taxpayers in both countries simultaneously buying securities of the other, or simultaneously buying their own domestic securities. It is also shown how we might find taxpayers of both countries buying the securities with the lower pretax yields.